The Hidden Cost of Untreated Paragangliomas of the Head and Neck: Systemic Reactive (AA) Amyloidosis - Erkan Dervisoglu; Murat Ozturk; Mehmet Tuncay; Gulhatun Kilic Dervisoglu; Yesim Gurbuz; Serhan Derin (Case Reports in Nephrology)
We report a case of a 51-year-old man who was diagnosed with systemic reactive (AA) amyloidosis in association with untreated glomus jugulare and glomus caroticum tumors. He refused radiotherapy and renal replacement therapy. Paragangliomas, although rare, should be considered one of the tumors that can result in AA amyloidosis.